Improving Students Writing Skills Through Canva Application at SMP Muhammadiyah Imogiri Yogyakarta - Fitri Andriyanti; Dwiyani Pratiwi; Dede Yunda (International Journal of Contemporary Studies in Education, 2023)
The objective of this study was to improve the writing abilities of students in Class VII E at SMP Muhammadiyah Imogiri, Yogyakarta by utilizing the CANVA application to write recount text. However, based on observation, several issues were identified, including inadequate writing skills among students, lack of interest in writing, the teacher's writing approach, the media's role, and limited internet access due to the school's prohibition of smartphones. Based on these observations, it was found that students faced difficulties in writing, particularly in terms of the generic structure. Additionally, they lacked knowledge on identifying and rectifying errors in their writing, as their English teacher predominantly focused on directly correcting their mistakes. This action research study comprised two cycles and included 25 students from Class VII E at SMP Muhammadiyah Imogiri, Yogyakarta. The study involved one English teacher as a collaborator and the researcher herself. Qualitative data was collected for this study. However, the qualitative data was gathered through observations of the teaching and learning process during the action implementation, as well as interviews conducted with the students and the collaborator regarding the implementation actions. Moreover, the qualitative data took the form of field notes and transcripts of the interviews. The findings of this study indicate that the utilization of the CANVA application is an effective method for improving students' writing skills, as supported by the analysis of qualitative data. The learning process became more engaging, and the students actively enjoyed the writing process. By incorporating the CANVA application into the teaching-learning process and employing writing activities through this platform, the challenges faced by students in writing were successfully mitigated.